2015
DOI: 10.1016/j.carbpol.2015.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Purified polysaccharides of Geoffroea spinosa barks have anticoagulant and antithrombotic activities devoid of hemorrhagic risks

Abstract: Polysaccharides were extracted from the barks of Geoffroea spinosa, purified using anion exchange chromatography and characterized by chemical and methylation analysis, complemented by infrared and NMR spectroscopies. These polysaccharides were tested for their anticoagulant, antithrombotic and antiplatelet activities and also for their effects on bleeding. Unfractionated polysaccharide contains low levels of protein and high levels of carbohydrate (including hexuronic acid). The purified polysaccharides (frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 43 publications
1
17
0
2
Order By: Relevance
“…Sulfated seaweed polysaccharides exhibit antioxidant activities, which are closely related to their physicochemical properties, such as molecular weight, −OSO 3 H content, and polyphenol content [58]. For example, Wang et al [7] extracted three components from Laminaria japonica (F1, F2, and F3) with sulfate contents of 23.30%, 36.41%, and 36.67%, respectively, and their ability of scavenging superoxide anion, hydroxyl radical, chelating ability, and reducing power all decreased in the order of F3 > F2 > F1, which suggested that sulfate content was positively related with the bioactivities of a polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfated seaweed polysaccharides exhibit antioxidant activities, which are closely related to their physicochemical properties, such as molecular weight, −OSO 3 H content, and polyphenol content [58]. For example, Wang et al [7] extracted three components from Laminaria japonica (F1, F2, and F3) with sulfate contents of 23.30%, 36.41%, and 36.67%, respectively, and their ability of scavenging superoxide anion, hydroxyl radical, chelating ability, and reducing power all decreased in the order of F3 > F2 > F1, which suggested that sulfate content was positively related with the bioactivities of a polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…[30] In the 13 C spectrum (Fig.4B), the strong presence of carbon chemical shifts at δ 103.9 ppm was assigned to the anomeric carbon of 6)-β-D-Glcp-(1→ residue with a high proportion. [11,33] According to reference data set, [24,[34][35][36][37][38][39] the resonances at δ 104.9, 109.8, 105.7, to the methyl carbon of rhamnose residues. [40] The weak signal in the region at δ 179.39 ppm originated from C-6 of the unesterified galacturonic acid unit.…”
Section: Chemical Analysis Of Shdpsmentioning
confidence: 99%
“…Recently, venous thrombus has developed into a major disease threatening human public health all over the world, but there are few effective anticoagulant drugs available in the market (Souza et al., 2015). As a kind of natural or synthetic polysaccharides with hydroxyl groups replaced by sulfuric acid groups (Li, Chi, Yu, Jiang, & Liu, 2017), sulfated polysaccharides are more and more attractive to researchers due to the excellent pharmacological properties, such as anticoagulation, antiviral, and anti‐inflammatory activities (Yu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%